A 29pJ/b FSK transmitter for wireless body area network application - Li, Yilie (2016)
The implantable and body-worn bio-medical devices have been the focused applications in the wireless body area network. To prolong the lifetime of these devices, we expect the circuits to be energy efficient, hence minimum power consumption and also increase data rate. In this thesis, the design and simulation results of a novel frequency shift keying (FSK) transmitters are presented. The first circuit is a 30 to 120 MHz FSK transmitter for wireless body area communication. Unlike the conventional transmitter, multiple injection locked modulation scheme is employed to achieve the FSK modulation. Using this method, both frequencies of the FSK transmitter are locked to the reference frequency. With injection lock, the frequency drift of a free running oscillator can be eliminated. A 9-bit ultra wide-band digitally controlled oscillator (DCO) is employed in this work. The DCO is controlled by a digital-to-analog converter (DAC) for frequency calibration and modulation of frequency. With 4-bit fine tuning and 5-bit coarse tuning, the DCO can cover a wide band from 30 to 120 MHz or even higher frequencies depending on the process parameters. In addition, a 9-bit MUX is used as the control circuit for the DAC. Implemented in 0.18-μm CMOS process, the transmitter is able to achieve a maximum data rate of 5 Mbps, with a core power consumption of 146 μW under 1.2-V power supply.